Of primary importance: applying the new literacy guidelines. Issue 2 (11th June 2018) - Hauck, Janet; Robinson, Marc
Abstract : Purpose: Written by a librarian and history professor, the purpose of this paper is to describe a collaborative, primary source literacy project and report its effectiveness in teaching undergraduates to critically analyze information and develop primary source literacy. Design/methodology/approach: The methodology used included a research project with 24 undergraduates and a pre- and post-survey. The research project and student survey incorporated principles from the "Guidelines for Primary Source Literacy", published in 2017 by the ACRL's Rare Books and Manuscripts Section and the Society of American Archivists. The paper offers research and practical implications for librarians and instructors interested in strategies to teach information literacy. For instance, the paper includes a review of literature on "archival intelligence" or "primary source literacy" and describes the 2017 Guidelines for Primary Source Literacy. Findings: Socially, the paper includes implications for how to create an inclusive learning experience for students with mechanisms such as a scaffolded assignment, hands-on instruction, imposter syndrome awareness and a no-Google policy. Originality/value: Given that this is one of the first articles to document how practitioners are incorporating the new 2017 Guidelines, this is sure to be an original and valuable essay.